Prevalence of second mesiobuccal canal in maxillary molars of Iranian population: A systematic review with meta-analysis. - Seyed Mohsen Hasheminia; Saber Khazaei; Pedram Iranmanesh; Jafar Kolahi; Bita Rasteh; Masoumeh Behdarvandi (PLoS ONE)
One of the main reasons for the failure of root canal treatment in maxillary molars is missing the second mesiobuccal (MB2) canal. This systematic review and meta-analysis aimed to estimate the prevalence of the MB2 canal in maxillary molars in the Iranian population.: Cross-sectional studies on the prevalence of MB2 canal in maxillary molars in the Iranian population were searched in PubMed, Scopus, Magiran, SID, IranMedex, and Google Scholar databases until 31 May 2024. The JBI Critical Appraisal Tool for prevalence studies was utilized for quality assessment. The prevalence of the MB2 canal was estimated with a 95% confidence coefficient (95%CI) using STATA18 software and the inverse variance method, separately for the first and second molars (CRD42024542862).In the present study, the prevalence of the MB2 canal in the maxillary first molar was 60% (95%CI, 53_67; I2 = 97.14%) and 33% (95%CI, 25_42; I2 = 97.42%) in the maxillary second molar. The highest prevalence rate of the MB2 canal in the maxillary first and second molars related to the microscope with 78% (95%CI, 54_101; I2 = 97.96%) and 61% (95%CI, 20_102%; I2 = 97.43%), respectively. The lowest prevalence rate of the MB2 canal in the maxillary first and second molars was related to the periapical radiograph with a rate of 15% (95%CI, -10_40; I2 = 91.17%) and 4% (95% CI, -8_17; I2 = 40.52%), respectively. The prevalence of the MB2 canal in the Iranian population in the first and second molars was 60% and 33%, respectively. This prevalence rate depended on the assessment methods.